Uma cilada chamada "raciocínio teórico sistemático" - Renan Springer de Freitas (2017)
In 1966 Peter Berger and Thomas Luckmann proposed to produce a “single body of systematic theoretical reasoning.” Now, fifty years later, it is clear that this project has failed. Not only this, but all those of the same nature. This article discusses the reasons for this failure. The basic argument is that the effort to produce such a “single body” is only justified when there is a rather specific problem requiring this kind of solution. When this condition is not previously satisfied, the engagement in this kind of project does not lead to a theoretical synthesis, as it is meant to do, but to a proliferation of “theoretical principalities”, as once said Robert Merton, which barely notice each other.